2020-2022 Arası TRT dizi filmlerinin yayın hayatına yansımaları - OKUMUŞ, MUHAMMED SAMİ (My University, 2022)
The purpose of the current study is to determine the released and discussed issues in the two-year period between 2020-2022, as the effect and planning of the TV series broadcasted from 1974 to the present by the Turkish Radio and Television Corporation (TRT), which carries out public broadcasting activities in Turkey and continues in the new broadcasting periods.The present study was designed to examine the information table which will include the names and detailed information of the TV series broadcast on TRT for the last two years in chronological order. The numbers, types, number of episodes, duration, first and last broadcast dates of the TV series released, as well as the information on which season they continue to broadcast, are also included in the table.The study explores that nine TV series were broadcast in 2020 and eight in 2021 on TRT. In addition to these numbers of TV series, comparisons were made with the genres of series broadcast on TRT as of 2010, which were determined from the previous study. According to this result between 2010 and 2022, there is a total of ninety TV series and fifty of them have a \"family\" genre, twenty-three of them have a \"historical\" genre. The results of this research support the information that television series productions about family and historical issues are on the screen in a total of 81% on the TRT channel.The study also tries to provide detailed information about the path and policies followed by TRT, which continues its broadcasts as an official state channel with the mission of public broadcaster, in terms of TV series broadcasting from past to present.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)